2018
DOI: 10.1111/inm.12463
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration as a process and an outcome: Consumer experiences of collaborating with nurses in care planning in an acute inpatient mental health unit

Abstract: This qualitative study explores inpatient mental health consumer perceptions of how collaborative care planning with mental health nurses impacts personal recovery. Semi-structured interviews were conducted with consumers close to discharge from one unit in Sydney, Australia. The unit had been undertaking a collaborative care planning project which encouraged nurses to use care plan documentation to promote person-centred and goal-focussed interactions and the development of meaningful strategies to aid consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 17 publications
2
56
0
1
Order By: Relevance
“…Informed by RSA, by a recovery-oriented practice we mean a practice integrating the patients' life goals, preferences, choices, and interests in terms of treatment plans, transferral, and discharge (O'Connell et al 2005). Similarly, in a study of patients' experiences of collaborating with health professionals in a systematic development of care plans based on personal goals, Reid et al (2018) found that, while patients appreciated the process of it, they did not find that their personal care plans were otherwise given any role or practical use. This is problematic given that recovery orientation not only entails collaboration between patients and health professionals but also requires that patients themselves and their personal experiences and preferences are recognized as the pivot points of any planning and provision of treatment and care (O'Connell et al 2005;Williams et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informed by RSA, by a recovery-oriented practice we mean a practice integrating the patients' life goals, preferences, choices, and interests in terms of treatment plans, transferral, and discharge (O'Connell et al 2005). Similarly, in a study of patients' experiences of collaborating with health professionals in a systematic development of care plans based on personal goals, Reid et al (2018) found that, while patients appreciated the process of it, they did not find that their personal care plans were otherwise given any role or practical use. This is problematic given that recovery orientation not only entails collaboration between patients and health professionals but also requires that patients themselves and their personal experiences and preferences are recognized as the pivot points of any planning and provision of treatment and care (O'Connell et al 2005;Williams et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This is problematic given that recovery orientation not only entails collaboration between patients and health professionals but also requires that patients themselves and their personal experiences and preferences are recognized as the pivot points of any planning and provision of treatment and care (O'Connell et al 2005;Williams et al 2015). Similarly, in a study of patients' experiences of collaborating with health professionals in a systematic development of care plans based on personal goals, Reid et al (2018) found that, while patients appreciated the process of it, they did not find that their personal care plans were otherwise given any role or practical use. This warrants an apprehension that even when recovery-oriented practices are formally acted out, they tend to remain superficial additions to practice rather than informing the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Reid, et al . () found a prevalent theme in their qualitative study of consumer experiences of care to be fear of becoming a bother as a response to nurses' apparent busyness. Consumer interpretation that the nurse is not available or amenable to interaction creates a barrier to relationship.…”
Section: Barriersmentioning
confidence: 99%
“…Conscious or unconscious communication of feelings of being busy overwhelmed or under time pressure may be interpreted quite differently by consumers. For example, Reid, et al (2018) found a prevalent theme in their qualitative study of consumer experiences of care to be fear of becoming a bother as a response to nurses' apparent busyness. Consumer interpretation that the nurse is not available or amenable to interaction creates a barrier to relationship.…”
Section: Barriers Timementioning
confidence: 99%
“…Emphasis is not on risk prediction; rather, management is informed by personal growth, whereby risk taking is seen as part of daily living, underpinned by understanding that risk involves having opportunities to make life more satisfying (RCP, ). For this to occur, Reid, Escott, and Isobel () propose that this requires clinicians to share power, so that patients have active roles with navigating their own safety. This is echoed in policy, in that promoting safety is not only an endpoint of risk management, but patients feel safe to engage in its practices (DH, ).…”
Section: Introductionmentioning
confidence: 99%